The senior co-housing prism: multiple perspectives about the practice, with an insight on the Spanish experience (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This contribution aims at assessing the topic of senior co-housing through four main points: an intergenerational perspective in reverse; the picture concerning the rights involved, from traditional ‘guarantees’, to new emerging claims; a comparative analysis of the Spanish system, vis-à-vis responses compliant with the Italian context, and its ongoing transformations; an intersectional approach, since the multiple sources and forms of discrimination stemming from identity. In addition, collaborative living implications on elderly people’s health will be addressed, as an innovative (and holistic) health ecosystem, at the same time analysing its benefits and shortcomings.
Keywords: Senior co-housing; longevity policies; right to health; active aging; aging in place